Innovative Pathways for the use of Excavation Materials in the Frame of the Future Circular Collider Project - Elisabeth Hauzinger; Luisa Ulrici; Johannes Gutleber; Robert Galler; Daniel Schneider; Maximilian Haas; Michael Benedikt; Mathieu Pillet; Jérémy Voiron; Pierre Boillon; Agathe Denot; Julie Paciello; et al. (Circular Economy and Sustainability, 2025)
Based a recommendation of the European strategy of particle physics of 2020 due to the great research success of the last decade CERN is planning a new circular collider with a circumference of approximately 91 km. To start construction in the middle 2030s a feasibility study is underway which includes scientific and financial components as well as territorial aspects such as geology, environment, technical infrastructure and civil engineering. One important factor is the management of the approximately 8 Mio. m3 of excavation materials, which consists mostly of molassic sediments of the Geneva Basin. In order to ensure that as much of the material as possible is put to high quality use in accordance with local regulations, the international contest “Mining the Future ® ” was launched. For this task geotechnical, mineralogical and geochemical tests were carried out on a large number of samples from across the study area. Based on the results, various utilization options were designed, which are primarily oriented towards alternative building materials with a low carbon footprint as well as agricultural use. The resulting concept of these sustainable strategies not only has a positive impact on the construction industry, but also play a major socio-economic role, as they improve social acceptance as well as responsibility in relation to large-scale projects.